GENERAL CLASSIFIER OF SYSTEM PROBLEMS - I: ANALYSIS, SYNTHESIS, VALIDATION AND VERIFICATION - Yu. I. Lobanovsky (Российский технологический журнал)
The upper level of a general classifier of system problems was constructed on the basis of system principles. This classifier was considered as an object of system engineering, and in accordance with its modern principles, the construction was started with the creation of the classifier functional structure. Further, requirements for this structure were validated. At the same time, as a result of the system problems analysis, taking into account the similarity of functional structures at the system level and at the level of its environ, six elements of its upper level were identified. Then the logical architecture of the classifier was constructed, and preliminary verification of the requirements was carried out. It was shown that the proposed structure of the general classifier of problems with one exception coincides with the structure of 5 causes of ecological disasters described in the book by J. Diamond "Collapse", if one replaces his ecological terminology by a system-wide one. The exception is one structural element of the general classifier of problems, which was not revealed in the empirical analysis of both system and ecological problems. Thus, the system-engineering approach in constructing the classifier allowed to create a more complete and adequate structure than a simple empirical examination of relevant data array. Classification of system problems helps to better understand the reasons why complex systems are not able to perform the tasks assigned to them. Therefore, it should be expected that the use of this classifier by system engineers will allow avoiding in the future those mistakes that led to failures in the past in the construction and/or development of complex systems.